The sedentarisation process of the Bahima in Uganda: an emic view - Wurzinger, Maria; Okeyo Mwai, Ally; Semambo, D.K.; Sölkner, Johann (2009)
The traditional lifestyle of nomadic pastoralists is vanishing rapidly, because of human population growth which often leads to land scarcity or political pressure on pastoralists to settle. The sedentarisation of the Bahima pastoralists in Western Uganda started in the 1940s and is still going on. In this study former nomadic cattle keepers, who have settled with their families, were interviewed in order to document the decision to settle and the subsequent changes in the lifestyle of these people. All interviewees expressed their satisfaction with their sedentary life. Land scarcity, access to education, better availability of water and the possibility of crop production were given as factors for settlement. The decisions were influenced by Christian missionaries, the government and friends.